Phase I dose-escalation trial of intravaginal curcumin in women for cervical dysplasia - Gattoc L; Frew PM; Thomas SN; Easley KA; Ward L; Chow HHS; Ura CA; Flowers L (Open Access Journal of Clinical Trials, 2016)
Leda Gattoc,1 Paula M Frew,2–4 Shontell N Thomas,5 Kirk A Easley,6 Laura Ward,6 H-H Sherry Chow,7 Chiemi A Ura,8 Lisa Flowers8 1Division of Gynecologic Oncology, Wayne State University, Detroit, MI, 2Division of Infectious Diseases, Department of Medicine, Emory University School of Medicine, 3Department of Behavioral Sciences and Health Education, 4Hubert Department of Global Health, 5Ochsner Medical Center, Kenner, LA, 6Department of Biostatistics and Bioinformatics, Rollins School of Public Health, Emory University, Atlanta, GA, 7Department of Medicine, University of Arizona, Tucson, AZ, 8Division of Gynecologic Oncology, Department of Obstetrics and Gynecology, Emory University School of Medicine, Atlanta GA, USA Background: This is a Phase I trial demonstrating safety and tolerability of intravaginal curcumin for future use in women with cervical neoplasia.Objective: The objective of this study was to assess the safety, tolerability, and pharmacokinetics of intravaginal curcumin in healthy women. Study design: We conducted a 3+3 dose-escalation Phase I trial in a group of women aged 18–45 years. Thirteen subjects were given one of four doses of curcumin powder (500 mg, 1,000 mg, 1,500 mg, and 2,000 mg) packed in gelatin capsules, which was administered intravaginally daily for 14 days. The primary end point for this study was safety based on severe adverse events regarding laboratory toxicity, clinical findings, and colposcopic abnormalities. We administered an acceptability questionnaire to assess product experience and attributes. Results: No dose-limiting toxicities (0/13) were experienced (95% confidence interval: 0.0%–22.8%) in this study. The pharmacokinetics data demonstrated that curcumin and curcumin conjugates were not measurable in the serum and negligible in the urine of the study participants. Although 23 adverse events occurred during the course of the trial, all events were grade I based on the National Cancer Institute Common Terminology Criteria for Adverse Events Version 4.0 and were resolved by the end of the study in an average of 9 days. Fifty-six percent of the adverse events were related to the study drug, which included genital pruritus (23% of subjects), vaginal discharge (100%), vaginal dryness (15%), abnormal prothrombin (23%), and hypokalemia (8%). Conclusion: Intravaginal curcumin was well tolerated by all subjects and safe. In this Phase I trial, there were no severe adverse events observed at any of the administered dose levels. All adverse events were grade I and did not result in early termination of the study. There was no evidence of systemic absorption or significant local absorption of intravaginally administered curcumin. Keywords: cervix, curcumin, intravaginal, safety, tolerability, neoplasia